Analisa Predictive Berbasis Supervised Machine Learning Terhadap Kerusakan Peralatan Pembangkit - Marte Ardhianto, Mochamad; Sumarwanto, Rudi (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
Predictive maintenance is a treatment for the actual operation of the equipment to optimize the company's operations. The output of predictive program maintenance is data, this treatment includes the type of